Экспериментальные исследования распределения продольной составляющей скоростей течения по глубине потока р. Риони - Шаутидзе (Shautidze Otar), Отар Давидович; Носелидзе (Noselidze Jondo), Джондо Владимирович; Момцемлидзе (Momcemlidze Shorena), Шорена Андреевна (Географический вестник=Geographical bulletin, 2017)
Представлены результаты экспериментального исследования продольной составляющей скоростей течения по глубине потока р. Риони в районе с. Сакочекидзе. Дано сопоставление полученных результатов с материалами расчетов по различным эмпирическим формулам. EXPERIMENTAL RESEARCHES OF DISTRIBUTION LONGITUDINAL COMPONENT OF SPEEDS OF CURRENT ON DEPTH OF RIONI RIVER Received fathom is compared to calculation size with Gaze, Korausevi and Prandtli-Karmanis empirical formulas. The speed empirics receiving used with Prandtli-Karmanis half empirical formula is agreement to fathom greatness well. The remained formulas offer dig differences. Ten speed empirics maybe divide the high gradient zone (bottom-0.5 H) and the low gradient zone (surface- 0.5 H).